Being young in Peru: Socialization, integration, corporeality and culture - Vega-Centeno Bocángel, Imelda (1993)
The first difficulty we encounter in studying young people as a social phenomenon is that there is no theoretical agreement that limits and characterizes the phenomenon in such a way that it can be defined, both in its peculiarities and in the complexity that its reality demands. If we review the different approaches with which the youth phenomenon has been studied, we first see the psychological —medical— approach, where the youth is studied as a set of psychological reactions to certain biological changes experienced in adolescence.